Climate Supercirculation Of The Earth - Ulaanbaatar, Tarzadin (Scientific transaction of the National University of Mongolia. Physics, 2022)
The objectives of this paper are, first, to determine the thermal regime on and near the Earth’s surface, second, to interpret the space-time changes of climate oscillation in accordance with its cause, trigger, feedback mechanisms and chains.